The Effect of Cross‐Border Mergers and Acquisitions on Earnings Quality: Evidence from China. (19th September 2016) - (Sara) Ding, Xiaoya; Mo, Jiaying; Zhong, Ligang
Abstract : Despite the fruitful research on the motives and outcomes of cross‐border mergers and acquisitions (M&As) of Chinese multinational corporations (MNCs), there has been scant research on the impact of cross‐border M&As on corporate governance. In this article, we fill the research gap by exploring whether cross‐border M&As may lead to an improvement in corporate governance of Chinese acquirers. In particular, we examine the impact of cross‐border M&As on earnings quality of Chinese MNCs. We find that the acquisition of a target firm from a developed country leads to a significant improvement on the acquirer's earnings quality. In comparison, the acquisition of a target from an emerging market does not have such an impact. Our results are robust to various corporate governance measures, alternative econometric methods, and controls of relevant firm characteristics and macroeconomic variables. Finally, we show that the effect of cross‐border M&As on earnings quality is more pronounced in non‐state‐owned enterprises (non‐SOEs) that have conducted large M&A deals. Our article offers new insight to the international business literature on latecomer perspective and liability of foreignness. © 2016 Wiley Periodicals, Inc .